The Colonel's Dream - Chesnutt, Charles W. (Charles Waddell), 1858-1932 (Salt Lake City, UT : Project Gutenberg, 2006)
"The Colonel's Dream" by Charles W. Chesnutt is a novel published in 1905. After selling his business, Colonel Henry French returns to his North Carolina hometown with his son, hoping for a brief nostalgic visit. Instead, he confronts the harsh reality of post-Civil War racial oppression and economic injustice. Determined to transform his segregated Southern town into an equal society, the Colonel challenges powerful local interests and deeply entrenched white supremacy. His ambitious dreams for social reform meet fierce resistance, personal tragedy, and violent opposition. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Colonel%27s_Dream
Release date is 2006-11-09
E-text prepared by Suzanne Shell, Jeannie Howse, and the Project Gutenberg Online Distributed Proofreading Team (http://www.pgdp.net/)
E-text prepared by Suzanne Shell, Jeannie Howse, and the Project Gutenberg Online Distributed Proofreading Team (http://www.pgdp.net)
Keywords: City and town life -- Fiction; Psychological fiction; Rich people -- Fiction; Race relations -- Fiction; North Carolina -- Fiction; Racism -- Fiction; Failure (Psychology) -- Fiction; United States -- History -- Civil War, 1861-1865 -- Veterans -- Fiction